Prevalence, Disability, and Management Patterns of Migraine in Korea: Nationwide Survey Data from 2009 and 2018 - Kim, Kyung Min; Cho, Soo-Jin; Shin, Hye Jung; Yang, Kwang Ik; Kim, Daeyoung; Yun, Chang-Ho; Chu, Min Kyung (Journal of clinical neurology (Seoul, Korea), 2021)
Identifying changes in the prevalence, disability, and management patterns of migraine is important for reducing the burden of this disease. However, data on the changes in these variables are scarce. We compared data obtained in the 2009 Korean Headache Survey and the 2018 Korean Sleep-Headache Survey. The 1-year migraine prevalence did not differ significantly between 2018 and 2009 [5.2% (114/2,200) vs. 6.0% (91/1,507), =0.492]. The number of days with missed activity due to headache during the previous 3 months was larger in the 2018 survey than in the 2009 survey [1.1±2.9 vs. 0.3±1.0 days (mean±standard deviation), =0.013]. The number of days with reduced productivity during the previous 3 months did not differ significantly between the two surveys (0.8±2.8 vs. 1.4±1.4 days, =0.679). The proportion of subjects with a substantial-to-severe headache impact (Headache Impact Test-6 score ≥56) was marginally larger in the 2018 survey than in the 2009 survey [42.1% (48/114) vs. 29.7% (27/91), =0.066]. The rate of lifetime medical consultations did not differ between the 2018 and 2009 surveys [34.2% (39/114) vs. 30.8% (28/91), =0.615]. Migraine prevalence was stable over the 9-year period between the surveys, but disability due to missed activity was greater in 2018 than in 2009 in Korea.